Prediction of caesarean section for arrest of descent during the second stage of labour - Samal, Sunil Kumar; Rathod, Setu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Friedman described the normal progress of labor in different curves for nulliparous and multiparous women in 1954. Any deviation from these curves during the second stage of labor is considered as failure to progress in the second stage of labor. The aim of the study is to define obstetrical risk factors for arrest of descent during the second stage of labour. Methods: All singleton, vertex, term deliveries with an unscarred uterus, between December 2013 to November 2016 (3 years) were included. Univariable and multivariable analysis were performed to investigate independent risk factors associated with arrest of descent during the second stage of labor. Results: The study included 7260 deliveries, of these 163 (3.3%) were complicated with arrest of descent during the second stage of labor. Using a multivariable analysis, the following obstetric risk factors were found to be significantly associated with arrest of descent: primigravida (RR=7.8, 95% CI=6.9-8.7, p<0.001), obesity (RR=1.8, 95% CI=1.6-2.0, p<0.001), short stature (RR=2.3, 95% CI=1.9-2.8, p<0.001), hypertensive disorders(RR=1.5, 95% CI=1.3-1.8,p<0.001), gestational diabetes(RR=1.5, 95% CI=1.2-1.8, p<0.001), free floating head before labour(RR=3.4, 95%CI=2.5-4.1, p<0.001), Occipito-posterior position(RR=3.3, 95% CI=2.1-4.5, p<0.002), Prelabour rupture of membrane (PROM) (RR=1.3, 95% CI=1.0-1.6, p<0.02), induction of labour (RR=2.2, 95% CI=1.0-3.4, p<0.03) and birth weight>3.5 kg (RR=2.2, 95% CI=2.0-2.4, p<0.001). Deliveries complicated by arrest of descent resulted in cesarean section in 67% and 34% vaginal delivery. Conclusions: In this era of increased public awareness and medicolegal events it is very crucial to assess and evaluate every woman in labor and to identify in advance the possibility of arrest in advanced labor so that a timely obstetric intervention possibly Cesarean section can prevent unnecessary maternal- fetal complications.